Betulin from Hedyotis hedyotidea ameliorates concanavalin A-induced and T cell-mediated autoimmune hepatitis in mice - ZHOU Yong-qin; WENG Xiu-fang; DOU Rui; TAN Xiao-sheng; ZHANG Tian-tian; FANG Jin-bo; WU Xiong-wen (Acta Pharmacologica Sinica, 2017)
Hedyotis hedyotidea has been used in traditional Chinese medicine for the treatment of autoimmune diseases. However, the mechanisms underlying for the effect remain unknown. We previously showed that, among 11 compounds extracted from H hedyotidea, betulin produced the strongest suppressive effect on T cell activation. Here, we examined the hepatoprotective effects of betulin against acute autoimmune hepatitis in mice and the mechanisms underlying the effects. Freshly isolated mouse splenocytes were stimulated with concanavalin A (Con A, 5 μg/mL) in the presence of betulin, the cell proliferation was assessed with CSFE-dilution assay. Mice were injected with betulin (10, 20 mg·kg-1·d-1, ip) for 3 d. One hour after the last injection, the mice were injected with Con A (15 mg/kg, iv) to induce acute hepatitis. Blood samples and liver tissues were harvested at 10 h after Con A injection, and serum transaminase levels and liver histopathology were detected; serum levels of proinflammatory cytokines, hepatic T lymphocyte ratios, and functional statuses of conventional T and NKT cells were also analyzed. Betulin (16 and 32 μmol/L) dose-dependently suppressed the proliferation of Con A-stimulated mouse splenocytes in vitro. In Con A-challenged mice, preinjection with betulin (20 mg·kg-1·d-1) significantly decreased the levels of proinflammatory cytokines IFN-γ, TNF-α and IL-6, and ameliorated liver injury. Furthermore, pretreatment with betulin (20 mg·kg-1·d-1) significantly inhibited the Con A-induced activation of NKT and conventional T cells, and decreased production of proinflammatory cytokines IFN-γ, TNF-α and IL-6 in these two cell populations. Betulin has immunomodulatory effect on overly activated conventional T and NKT cells and exerts hepatoprotective action in mouse autoimmune hepatitis. The findings provide evidence for the use of H hedyotidea and its constituent betulin in the treatment of autoimmune diseases.